2015
DOI: 10.1371/journal.pone.0126561
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Markers Induced by Hyperosmolarity in Primary Human Corneal Epithelial Cells

Abstract: Oxidative stress has been known to be involved in pathogenesis of dry eye disease. However, few studies have comprehensively investigated the relationship between hyperosmolarity and oxidative damage in human ocular surface. This study was to explore whether and how hyperosmolarity induces oxidative stress markers in primary human corneal epithelial cells (HCECs). Primary HCECs were established from donor limbal explants. The hyperosmolarity model was made in HCECs cultured in isosmolar (312 mOsM) or hyperosmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 61 publications
(62 reference statements)
5
118
0
4
Order By: Relevance
“…1 Even if the changes are limited to altering tear film makeup and/or declines in secretion, tear film hyperosmolarity may develop and ultimately induce increases in reactive oxygen species (ROS) formation and inflammation. 2 These pathophysiologic effects are characteristic in some cases of dry eye (DE) disease and Sjögren's syndrome. [3][4][5] In corneal epithelial cells, we showed that hyperosmotic and oxidative stresses induce immune cell activation and inflammation as a consequence of assembly of the ROS-induced NLRP3 inflammasome-IL-1b signaling axis.…”
Section: Resultsmentioning
confidence: 99%
“…1 Even if the changes are limited to altering tear film makeup and/or declines in secretion, tear film hyperosmolarity may develop and ultimately induce increases in reactive oxygen species (ROS) formation and inflammation. 2 These pathophysiologic effects are characteristic in some cases of dry eye (DE) disease and Sjögren's syndrome. [3][4][5] In corneal epithelial cells, we showed that hyperosmotic and oxidative stresses induce immune cell activation and inflammation as a consequence of assembly of the ROS-induced NLRP3 inflammasome-IL-1b signaling axis.…”
Section: Resultsmentioning
confidence: 99%
“…SOD and CAT, the main cellular antioxidant enzymes, function mutually to scavenge ROS produced during the oxidative stress 26 . SOD converts the superoxide into hydrogen peroxide 27 , while CAT can then catalyze it into toxic free substances 28 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…38 Upregulation of COX-2 is a common feature of inflammation caused by oxidative stress. [38][39][40][41] Manganese-dependent superoxide dismutase is an antioxidant enzyme and has a critical role in scavenging ROS. 40 As shown in Figure 5, H 2 O 2 pretreatment dramatically reduced the levels of the PRX family proteins, MnSOD and CAT, and increased the level of COX-2.…”
Section: Effect Of Cj Extracts On Anti-inflammatory and Antioxidativementioning
confidence: 99%